Synergistic effect of CdS/GO nanocomposite for enhanced electrochemical performance in symmetric supercapacitor - Tabassum Ferdous; Muhammad Sajjad; Muhammad Yaqoob Khan; Inam Ullah; Samreena Firdous; Muhammad Shahid Khan; Nasim Ullah; Abid Zaman (Materials Research Express)
Metal sulfides and graphene oxide nanocomposites have recently has garnered considerable attention in the field of electrochemical energy storage devices. In this study, we synthesized a cadmium sulfide/graphene oxide (CdS/GO) nanocomposite using different contents of graphene oxide (0.01, 0.02, 0.03 and 0.04 g) with fixed concentartion of CdS (0.3 g) via Solid-State Reaction (SSR) method. CdS/GO composite were subsequently investigated to be used as electrode materials for supercapacitors. Notably, the optimized electrode CdS/GO-0.04 electrode demonstrated superior capacitive performance compare to individual CdS and their composites with GO. In a symmetric supercapacitor configuration, the CdS/GO-0.04 cathode demonstrated a specific capacitance of 211.5 F g ^−1 at a scan rate of 1.5 A g ^−1 and maintained 93% of its capacitance after 1,000 cycles at a current density of 5 A g ^−1 , indicating excellent cycling stability. The significantly improved capacitive performance of CdS/GO-0.04 can be primarily attributed to the synergistic interaction between CdS and GO particles, enhanced conductivity, and the relatively larger surface area of the composites. These findings suggest that CdS/GO nanocomposites hold great promise as electrode materials for high-performance energy storage applications.